An ion beam spot size monitor based on a nano-machined Si photodiode probed by means of the ion beam induced charge technique. (November 2022) - Andrini, G.; Nieto Hernández, E.; Provatas, G.; Brajkovic, M.; Crnjac, A.; Tchernij, S. Ditalia; Forneris, J.; Rigato, V.; Campostrini, M.; Siketic, Z.; Jaksic, M.; Vittone, E.
Abstract: In this work the utilization of the Ion Beam Induced Charge (IBIC) technique is explored to assess the resolution a 2 MeV Li + ion microbeam raster scanning a micrometer-sized FIB-machined hollows in a silicon photodiode. The analysis of the maps crossing the FIB machined structures evidenced a drop in charge collection efficiency across the perimeter of the hollows combined with a significant recovery of the signal amplitude at the center of the microstructures, thus forming a micrometer-sized feature which can be exploited to estimate the resolution of the probing beam. The results were interpreted according to numerical simulations based on the Shockley-Ramo-Gunn as originating from a FIB-induced surface space charge density. These results offered additional information with respect to what achievable by a confocal photocurrent microscopy analysis of the same device, due to the significantly shorter focal depth of the latter with respect to the probing ion beam. This study suggests the viability of an effective method to evaluate of the resolution of ion microbeams in processes and experiments, which could be beneficial in emerging fields (deterministic implantation, micro-radiobiology, ion lithography) demanding beam spot sizes below the micrometer scale. Highlights: A custom silicon photodiode was fabricated with custom sized hollows by FIB milling with nanoscale resolution. Photocurrent mapping under 445 nm excitation enabled to estimate the laser probe spatial resolution with sub-μm precision. Ion beam microscopy was performed on the same nanostructures using 2 MeV Li + ions. The ion beam FWHM was estimated by fitting the charge collection maps acquired via Ion Beam Induced Charge (IBIC) technique. IBIC results were validated by numerical modeling, offering insight on the formation and spatial distribution of the signal. The IBIC estimation of the ion beam FWHM was compared with Scanning Tranmission Ion Microscopy based on a reference standard.